A new three-term conjugate gradient method for solving nonlinear unconstrained optimization problems - Hussein Saleem Ahmed; Salah Gazi Shareef (Journal Focus Action of Research Mathematic (Factor M), 2025)
This study introduces a new development of the three-term conjugate gradient (TTCG) method. This method is used to solve unconstrained nonlinear optimization problems. The core of this development lies in the formulation of new β parameters, which then form a β-system in the proposed method. These parameters make the search direction more stable, enable it to follow the trajectory of change more smoothly, and accelerate convergence by reducing the number of iterations required. To assess its performance, the developed TTCG method is tested on several standard test functions and compared with the Liu–Storey (LS) method. All numerical calculations are performed in Fortran, while data visualization is implemented using Matplotlib in Python and ggplot2 in R. Based on experiments conducted, the TTCG method with the new β-system tends to reach solutions more quickly and yields more consistent results than the LS method for larger problem dimensions. Overall, the TTCG approach offers a more efficient, stable, and reliable alternative for solving unconstrained nonlinear optimization problems.